2010
DOI: 10.1128/aac.00764-10
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Distribution of Plasmids Bearing the bla OXA-51 -Like Gene with an Upstream IS Aba1 in Carbapenem-Resistant Acinetobacter baumannii Isolates in Taiwan

Abstract: The bla OXA-51 -like gene with an upstream ISAba1 (ISAba1-bla OXA-51 -like gene) was originally found on the chromosomes of carbapenem-resistant or -susceptible Acinetobacter baumannii isolates. However, a plasmidborne ISAba1-bla OXA-51 -like gene has recently been identified in Acinetobacter genomic species 13TU and several A. baumannii isolates in Taiwan, and all of the isolates are carbapenem resistant. This study aimed to characterize the plasmids bearing the ISAba1-bla OXA-51 -like gene and their signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
90
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 22 publications
6
90
2
Order By: Relevance
“…33 However, it is important to note that in a recent publication by Chen et al, 49.6% (58/117) of A. baumannii isolates that were obtained from 10 Taiwanese hospitals contained the OXA-51-like gene on a plasmid which conferred increased rates of resistance to imipenem and meropenem. 34 This phenomenon can be explained by the increased gene expression because of the higher copy number on the plasmids. 34 During M-PCR II, one of the isolates (isolate number 36) tested positive for the VIM-like gene, as well as for OXA-23 and OXA-51, indicating that this was a highly drug-resistant isolate of A. baumannii.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…33 However, it is important to note that in a recent publication by Chen et al, 49.6% (58/117) of A. baumannii isolates that were obtained from 10 Taiwanese hospitals contained the OXA-51-like gene on a plasmid which conferred increased rates of resistance to imipenem and meropenem. 34 This phenomenon can be explained by the increased gene expression because of the higher copy number on the plasmids. 34 During M-PCR II, one of the isolates (isolate number 36) tested positive for the VIM-like gene, as well as for OXA-23 and OXA-51, indicating that this was a highly drug-resistant isolate of A. baumannii.…”
mentioning
confidence: 99%
“…34 This phenomenon can be explained by the increased gene expression because of the higher copy number on the plasmids. 34 During M-PCR II, one of the isolates (isolate number 36) tested positive for the VIM-like gene, as well as for OXA-23 and OXA-51, indicating that this was a highly drug-resistant isolate of A. baumannii. Antimicrobial susceptibility testing with the Vitek 2 Automated System ® confirmed that isolate number 36 was resistant to gentamicin, ceftazidine, piperacillin-tazobactam, ciprofloxacin, imipenem, cefepime and meropenem.…”
mentioning
confidence: 99%
“…The bacterial genus Acinetobacter is recognized as a key HAI-causing pathogen that is associated with high mortality rates in hospital settings (2) (4) . Acinetobacter has considerable capacity to spread and develop new antibiotic resistance mechanisms (5) . Consequently, numerous HAI outbreaks caused by multidrug-resistant (MDR) representatives of the Acinetobacter calcoaceticus-Acinetobacter baumannii complex have been reported in several countries, including Brazil (2) (5) (6) .…”
Section: Introductionmentioning
confidence: 99%
“…1). This gene had a genetic environment identical to that of the chromosomal bla OXA-51 gene in A. baumannii (19), which includes two genes that are usually present upstream and downstream of bla OXA-51 in A. baumannii, the phosphinothricin Nacetyltransferase-encoding gene and fxsA, respectively. bla has 95% identity with the previously reported bla OXA gene (GenBank accession number CP002177, locus tag BDGL_000903) from the genome of A. calcoaceticus PHEA-2 (20), which is the closest neighbor of our CR12-42 isolate, as previously mentioned.…”
mentioning
confidence: 99%